Dairy Products Added in Media Affect the Development of Drosophila melanogaster (Diptera: Drosophilidae). Issue 3 (12th June 2018) - Karatas, Ayla; Ozgumus Demir, Emel
Abstract: Due to the increased interest shown in kefir, the present study examined its effects on some developmental characteristics in Drosophila . To compare the results related to kefir, another fermented product, i.e., yogurt, and the raw material of kefir, i.e., milk, were included in the experiment. All three foods were fed to Drosophila by addition to the medium. The results showed that the three foods delayed development in generations F1 and F2 . In both generations, the number of adults was lower than that of the control group, but the comparison of the foods among themselves showed no significant difference. Moreover, the negative effect continued in generation F2 . Phenotypically abnormal individuals were observed in the experiments, but there was no significant difference. Furthermore, the sex ratio changed in all the groups, including the control group. In the experimental group fed kefir, the sex ratio changed in favor of females, whereas in the other groups, it changed in favor of males. Whether the milk and milk products were fermented did not change the effect on Drosophila, but unexpectedly it delayed development, reduced the number of adults, and changed the sex ratio. It can be concluded that the three foods delayed development and altered the sex ratio in Drosophila .